Undergraduate students' norms for the Chinese version of the symptom check-List-90-R (SCL-90-R) - Yulan Yu; Chonghua Wan; Xudong Zhao; E. Scott Huebner; Jianfeng Tan; Chuanzhi Xu; Jingjing Zhang (BMC, 2020)
Abstract Background Despite widespread application of the Symptom Check-List-90-R (SCL-90-R) for Chinese undergraduate students, there are no appropriate norms for them. The aim of this study is to provide norms for the Chinese version of the tool for undergraduate students using a large and representative sample. Methods Four thousand eight hundred sixty students completed the scale of SCL-90. The mean scores obtained in the present study were compared with mean scores from previous normative samples. Results The mean scores for nine subscales of the SCL-90-R ranged from (1.36 ± 0.46) ~ (1.77 ± 0.63) and the mean (standard deviation) Global Severity Index (GSI) was 1.50 (0.49). Relative to previous normative studies, the findings suggested that Chinese undergraduate students' self-reported mental health symptoms decreased in interpersonal sensitivity, depression, hostility, and paranoid ideation subscales. Conclusion It is necessary to revise the norms of the Chinese version of the SCL-90-R for undergraduate students.